Corruption and Its Impact on Foreign Direct Investment - Linhartová, Veronika; Vávrová, Daniela (SciencePark Research, Organization and Counseling, 2017)
Some studies show the negative impact of corruption on FDI inflows. The high level of corruption can cause a direct reduction of FDI because of the bad reputation of the country abroad. Recent studies, however, also point to a possible reverse trend where countries with higher corruption are for some investors very attractive. This paper focuses on verification of the existence of relationship between the level of corruption and FDI and the impact of corruption on FDI in selected group of countries in period 1998-2015. The use of correlation analysis reveals a significant relationship between FDI and corruption. Regression analysis reveals the negative impact of corruption on FDI, particularly in countries with high levels of corruption. This analysis confirms the dependence of FDI on the level of corruption in the country especially in countries with a high level of corruption. Fighting corruption could be considered as a tool supporting investment inflows in these countries.
Korupce a jej9 vliv na p59m0 yahrani4n9 investice
Keywords: Corruption; foreign direct investment (FDI); Corruption perception index (CPI); correlation analysis, regression analysis.; Korupce; přímé zahraniční investice (PZI); Index vnímání korupce (CPI); korelační analýza, regresní analýza